Congenital cytomegalovirus in eastern Uganda: prevalence and outcomes - Noela Regina Akwi Okalany; Ingunn Marie S. Engebretsen; David Mukunya; Martin Chebet; Francis Okello; Andrew D. Weeks; Edrin Mwanda; Rita Muhindo; Fred Bisso; Thorkild Tylleskär; Peter Olupot-Olupot; Kathy Burgoine (BMC Pediatrics)
Abstract Background Cytomegalovirus (CMV) infection poses risks to both maternal and neonatal health, however there are limited comprehensive data on congenital CMV in low-resource settings where the virus is widespread, particularly among women of reproductive age. Our research in eastern Uganda aimed to assess the prevalence of congenital CMV and outcomes among infants to inform public health policies and interventions in similar settings, addressing a significant gap in current knowledge. Methods We conducted a descriptive study, nested within the BabyGel Trial, across Mbale and Budaka districts in eastern Uganda, between May 2023 and January 2024. Infants underwent saliva sampling within the first week of life, which was validated through urine polymerase chain reaction testing within the first 21 days of life. At three months of age, a cranial ultrasound examination, neurological examination, developmental evaluation, and audiological assessment were conducted for all infants diagnosed with congenital CMV infection. Statistical analyses were performed using Stata 17.0. Results Congenital CMV infection was found in 5 out of 1,265 newborns tested, indicating a prevalence of 0.4% (95% CI: 0.16 to 0.96). Of these 5 infected infants, two experienced febrile illness at birth and required hospitalisation within the first week of life, and three had findings on ultrasound examination consistent with congenital cytomegalovirus during the neonatal period. Audiologic follow-up until three months of age revealed that three infants had failed unilateral and bilateral hearing screening. Neurodevelopment assessments using the Malawi Development Assessment Tool fell within optimal ranges for all 5 infants; however, when evaluated using the Hammersmith Infant Neurological Examination, four infants scored below optimal levels. Conclusion Our community-based study revealed a low prevalence of congenital CMV infection. Further longitudinal multi-site research is needed to assess the generalisability of these findings. Also, long-term follow-up of children is crucial to understanding the outcomes and sequelae of infected infants to inform prevention strategies, targeted interventions and scalable screening frameworks in resource-limited settings.